The Development and Structure of Nomination Committees in Iceland - Hildur Magnúsdóttir 1985- (2020)
Nomination Committees, which nominate corporate board directors, have recently emerged in the context of corporate governance, both in Iceland and other countries; most Icelandic-listed firms have now established them. There are different academic and business world opinions on the committees’ rationale, procedures, and structure. The committees are operated in different ways within Nordic corporate governance norms, i.e., they are either directly subordinate to shareholders or appointed as board sub-committees. Previous research on nomination committees shows that their existence can positively affect corporate governance, and that their work can lead to a better process for appointing directors. The committees have not been examined in Iceland before and this study aims to document original insight into their organization and work. Interviews were conducted with thirteen individuals who are shareholders, board members of listed companies, or committee members. In addition, a questionnaire prepared in collaboration with the Iceland Chamber of Commerce and sent to shareholders, board members, nomination committee members, and the 300 largest companies in Iceland was used. The main outcomes indicated that the process of appointing board members in Iceland is more professional if nomination committees are in place. It was also considered more successful for the committees to be shareholders’ committees and that board members be elected by them at shareholders' meetings. It was also deemed useful to appoint board members that are retiring from the board as committee members. Shareholders' interest in nomination committees has increased in recent years. However, they are not apparently as satisfied with the existence and activities of the committees as are board members and nomination committee members. Most of the interviewees felt that the committees are beneficial for good corporate governance and that they will continue to be supported, at least in listed companies. The study supports the main findings of ...